Design of Manufacturing Processes for the Cold Bulk Forming of Small Metal Components from Metal Strip - Stellin, Tommaso (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2017)
The major objective of the work is to generate a basic understanding of manufacturing small metal component from metal strip, in order to reduce the handling limits in multi-stage microforming processes. The design supported by FE-modelling allows a simultaneous analysis of microforming process and strip deformation, in order to ensure a precise handling system. The selection of appropriate process parameters, together with the adoption of harder and thinner raw material, improves the material flow-control and an increase of the microscopic workpiece volume with a simultaneous achievement of a stable process conforming to mass-productio

Experimental and Numerical Investigation on a Full Forward Extrusion Process from Metal Strip - Stellin, Tommaso; Merklein, Marion; Engel, Ulf (Proc. 9th Int. Conf. Multi-Material Micro Manufacture, 2012)
LFT Import::2019-08-05 (1844)

Experimental Study of a Full Forward Extrusion Process from Metal Strip - Merklein, Marion; Stellin, Tommaso; Engel, Ulf (Key Engineering Materials, 2012)

Experimental Study of a Microforging Process of Parallel Ribs from Metal Strip - Stellin, Tommaso; Engel, Ulf; Merklein, Marion (Proc. 4M/ICOMM2015 Conf., 2015)
LFT Import::2019-08-05 (2100)

Investigation on a Microextrusion Process of Parallel Protrusions from Metal Strip - Stellin, Tommaso; Merklein, Marion; Engel, Ulf (Proc. 8th Int. Conf. Micro Manufacturing, 2013)
LFT Import::2019-08-05 (1898)

Modelling and experimental study of a microforging process from metal strip for the reduction of defects in mass production - Stellin, Tommaso; Van Tijum, Redmer; Engel, Ulf (Production Engineering, 2016)
Microforming from sheet metals is a technology with high potential and increasing interest in modern factories. The combination of bulk forming technologies in micro-scale together with the easier handling of metal strips allows the high rate production of products with small dimension and is suited for commercial fields like electronics and micromechanics. The need of an efficient FEM aided process design must face the problem of material behavior in microforming, affected by size-effects and not obeying continuum mechanics. A reliable FE model allows the production of a database allowing, additional to process optimization, the design of online process control and the reduction of manufacturing defects, strongly affecting micro-productions because of the high deviations in such processes. In this work, a method for the design of a FEM model of a microforging process is proposed, developed in the commercial software MSC Marc including the modelling of local size effects in the form of variable friction. An increased friction factor is assumed, where typical microforming size effects are expected to take place. Stainless steel and copper-beryllium alloys are studied with the thickness of 300 µm. The microforged geometry consists in 6 parallel protrusions with a width of 200 µm. The experimental study is then performed, by varying punch forces, firstly in a simplified configuration with two protrusions and finally with the complete geometry in a multi-stage microforming process, respectively validating and verifying the developed simulation model.
LFT Import::2019-07-29 (2163)
Keywords: Copper-beryllium; Microforming; Numerical simulation; Sheet-bulk forming; Stainless steel

Modification of Tribological Conditions for Influencing the Material Flow in Bulk Forming of Microparts from Sheet Metal - Kraus, Martin; Andreas, Kolja; Stellin, Tommaso; Engel, Ulf; Merklein, Marion (AIP Conference Proceedings 1896, 2017)
LFT Import::2019-08-05 (2269)

Simulation of a Full Forward Extrusion Process from Metal Strip - Merklein, Marion; Stellin, Tommaso; Engel, Ulf (AIP Conference Proceedings, 2011)
The interest on mass production of small complex metal components is currently fostered by fields like electronics and micromechanics. A possible approach is seen in a multi-step bulk forming process, limited among scaling problems by handling difficulties between the forming stages. A radical simplification of the positioning of the workpiece is seen in a process in which a metal strip acts both as raw material and support of the workpiece through the different forming stages. Within the study of this method, a full forward extrusion process from metal strip has been simulated with the goal of getting the basic knowledge about the strip behavior and process performance. The influence of the main geometric and tribological features has been evaluated designing a full factorial plan. The role of the radius of curvature of the tool edges and of the factor of friction have become the points of main interest in the optimization of the process. © 2011 American Institute of Physics.
LFT Import::2019-07-29 (1636)
Keywords: full forward extrusion; metal strip forming; microforming

Simulationsbasierte Untersuchung eines neuartigen Fügekonzepts für Rotoren elektrischer Maschinen - Frey, Philipp; Hildering, Sven; Tsoupis, Ioannis; Stellin, Tommaso; Merklein, Marion (Tagungsband 17. RoundTable - Simulating Manufacturing, 2016)
LFT Import::2019-08-05 (2171)

Study of Microforging of Parallel Ribs from Metal Strip - Stellin, Tommaso; Van Tijum, Redmer; Merklein, Marion; Engel, Ulf (Material Forming - ESAFORM 2014, 2014)
The on-going trend in product miniaturization, together with the increasing quality and reduction of costs of micro-components, leads to the need of a robust process design, which might additionally avoid the occurrence of defects in the workpiece. Processes like microforming are affected by variations which can be foreseen but not totally mastered in the design stage. One approach is seen in an adaptive control system based on a metamodel processing the data of online measuring. This approach is grounded on in-depth knowledge based on correct and precise process modelling. This paper presents both experimental and simulative study of a microforging process, part of a more complex forming chain. It consists of six parallel ribs on metal strip. The ribs have a width of 250 μm and are spaced by a gap of 150 μm. The process has been studied by different punch forces, analyzing the final geometry of the workpiece. In particular the rib height is considered as critical to quality parameter. The simulations show reliable results that can be used for the design of the model interfacing measurement and control of the whole microforming process. © 2014 Trans Tech Publications, Switzerland.
LFT Import::2019-08-05 (2040)
Keywords: Microforging; Sheet-bulk metal forming; Stainless steel